The Concept of Si Tou Timou Tumou Tou in Minahasa Philosophy as Strengthening Religious Moderation in Laikit Village - Rogahang, Heldy Jerry; Massang, Berdinata; Yandeyoa, Patresia E. (Peneliti.net, 2023)
Minahasa local wisdom and Christian tradition have spiritual, moral and social values in addressing contemporary issues surrounding interfaith relations. This article aims to analyze and describe the concept of Si Tou Timou Tumou Tou in Minahasa philosophy based on Matthew 22:39 as a strengthening of religious moderation in Laikit village, North Minahasa. The community in Laikit village which is plural from ethnicity, race, religion and inter-group elements does not make people coexist disharmoniously. Differences become a place to enrich, support, help and equip each other as fellow human beings. This research uses descriptive qualitative research methods, with data collection techniques through observation, interviews and document studies. Through this research it was found; first, the philosophy of Si Tou Timou Tumou Tou contributes to the strengthening of religious moderation in Laikit village, North Minahasa, which is manifested in solidarity, openness, mutual love/help, discipline. Second, Jesus' teaching in Matthew 22:39 becomes the principle of Christian life in the midst of diversity. Christians are called to be others for others. Third, the integration of the philosophy of Si Tou Timou Tumou Tou in the light of Matthew 22:39 is relevant and appropriate to create tolerance between religious communities, strengthening through integrating local wisdom values and biblical values is significant. The implementation of strengthening religious moderation based on local and theological wisdom can improve the quality of harmonious life in the community.